(4.x-3)^4=(4.x-3)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
4 x 2 x 5 = ?
Cách 1: 4 x 2 x 5 = (4 x 2) x 5 = 8 x 5 = 40
Cách 2: 4 x 2 x 5 = 4 x (2 x 5) = 4 x 10 = 40
7 x 2 x 3 = ?
Cách 1: 7 x 2 x 3 = (7 x 2) x 3 = 14 x 3 = 42
Cách 2: 7 x 2 x 3 = 7 x (2 x 3) = 7 x 6 = 42
6 x 3 x 3 = ?
Cách 1: 6 x 3 x 3 = (6 x 3) x 3 = 18 x 3 = 54
Cách 2: 6 x 3 x 3 = 6 x (3 x 3) = 6 x 9 = 54
6 x 2 x 4 = ?
Cách 1: 6 x 2 x 4 = (6 x 2) x 4 = 12 x 4 = 48
Cách 2: 6 x 2 x 4 = 6 x (2 x 4) = 6 x 8 = 48
a) 2 x 2 = 4 3 x 3 = 9
2 x 4 = 8 3 x 5 = 15
2 x 6 = 12 3 x 7 = 21
2 x 8 = 16 3 x 9 = 27
4 x 4 = 16 5 x 5 = 25
4 x 2 = 8 5 x 7 = 35
4 x 6 = 24 5 x 9 = 45
4 x 8 = 32 5 x 3 = 15
b) 200 x 4 = 800 300 x 2 = 600
200 x 2 = 400 300 x 3 = 900
400 x 2 = 800 500 x 1 = 500
100 x 4 = 400 100 x 3 = 300
Học sinh nhẩm và ghi kết quả như sau:
3 x 4 = 12 2 x 6 = 12 4 x 3 = 12 5 x 6 = 30
3 x 7 = 21 2 x 8 = 16 4 x 7 = 28 5 x 4 = 20
3 x 5 = 15 2 x 4 = 8 4 x 9 = 36 5 x 7 = 35
3 x 8 = 24 2 x 9 = 18 4 x 4 = 16 5 x 9 = 45
3 x4 = 12
3 x7 = 21
3 x5 = 15
3 x8 =24
2 x 6= 12
2 x8 = 16
2 x4 =8
2 x9 =18
4 x3 =12
4 x7 =28
4 x9 =36
4 x4 =16
5 x6 =30
5 x4 =20
5 x7 =35
5 x9 =45
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
1:
a: \(\left(2x-5\right)^2-4x\left(x+3\right)\)
\(=4x^2-20x+25-4x^2-12x\)
=-32x+25
b: \(\left(x-2\right)^3-6\left(x+4\right)\left(x-4\right)-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=x^3-6x^2+12x-8-\left(x^3-8\right)-6\left(x^2-16\right)\)
\(=-6x^2+12x-6x^2+96=-12x^2+12x+96\)
c: \(\left(x-1\right)^2-2\left(x-1\right)\left(x+2\right)+\left(x+2\right)^2+5\left(2x-3\right)\)
\(=\left(x-1-x-2\right)^2+5\left(2x-3\right)\)
\(=\left(-3\right)^2+5\left(2x-3\right)\)
\(=9+10x-15=10x-6\)
2:
a: \(\left(2-3x\right)^2-5x\left(x-4\right)+4\left(x-1\right)\)
\(=9x^2-12x+4-5x^2+20x+4x-4\)
\(=4x^2+12x\)
b: \(\left(3-x\right)\left(x^2+3x+9\right)+\left(x-3\right)^3\)
\(=27-x^3+x^3-9x^2+27x-27\)
\(=-9x^2+27x\)
c: \(\left(x-4\right)^2\left(x+4\right)-\left(x-4\right)\left(x+4\right)^2+3\left(x^2-16\right)\)
\(=\left(x-4\right)\left(x+4\right)\left(x-4-x-4\right)+3\left(x^2-16\right)\)
\(=\left(x^2-16\right)\left(-8\right)+3\left(x^2-16\right)\)
\(=-5\left(x^2-16\right)=-5x^2+80\)
1:
\(\Leftrightarrow\left(x^2+5x+6\right)\left(x^2+5x+4\right)=24\)
\(\Leftrightarrow\left(x^2+5x\right)^2+10\left(x^2+5x\right)=0\)
\(\Leftrightarrow x^2+5x=0\)
=>x=0 hoặc x=-5
3: \(\Leftrightarrow\left(x^2+x+6\right)\left(x^2+x-2\right)=0\)
=>(x+2)(x-1)=0
=>x=-2 hoặc x=1
`x + 2 3/4 = 5 2/3`
`=> x + 11/4 = 17/3`
`=> x= 17/3 -11/4`
`=>x=35/12`
__
`x - 1 4/5 = 3 2/7`
`=> x- 9/5 = 23/7`
`=> x= 23/7 +9/5`
`=>x=178/35`
__
`x xx 3 1/2 =4 3/4`
`=> x xx 7/2 =19/4`
`=> x= 19/4 : 7/2`
`=> x= 19/4 xx 2/7`
`=> x= 19/14`
__
`x : 2 2/3 = 4 1/3`
`=> x : 8/3 = 13/3`
`=> x= 13/3 xx 8/3`
`=>x=104/9`
a: =>x+11/4=17/3
=>x=17/3-11/4=68/12-33/12=35/12
b: =>x-9/5=23/7
=>x=23/7+9/5=178/35
c: =>x*7/2=4,75
=>x=19/4:7/2=19/14
d: =>x:8/3=13/3
=>x=13/3*8/3=104/9
a) \(x+2\dfrac{3}{4}=5\dfrac{2}{3}\)
\(x+\dfrac{11}{4}=\dfrac{17}{3}\)
\(x=\dfrac{17}{3}-\dfrac{11}{4}\)
\(x=\dfrac{35}{12}\)
b) \(x-1\dfrac{4}{5}=3\dfrac{2}{7}\)
\(x-\dfrac{9}{5}=\dfrac{23}{7}\)
\(x=\dfrac{23}{7}+\dfrac{9}{5}\)
\(x=\dfrac{178}{35}\)
c) \(x\times3\dfrac{1}{2}=4\dfrac{3}{4}\)
\(x\times\dfrac{7}{2}=\dfrac{19}{4}\)
\(x=\dfrac{19}{4}\div\dfrac{7}{2}\)
\(x=\dfrac{19}{14}\)
d) \(x\div2\dfrac{2}{3}=4\dfrac{1}{3}\)
\(x\div\dfrac{8}{3}=\dfrac{13}{3}\)
\(x=\dfrac{13}{3}\times\dfrac{8}{3}\)
\(x=\dfrac{104}{9}\)
a) \(...=x+\dfrac{11}{3}=\dfrac{17}{3}\Rightarrow x=\dfrac{17}{3}-\dfrac{11}{3}=\dfrac{6}{3}=2\)
b) \(...\Rightarrow x-\dfrac{9}{5}=\dfrac{23}{7}\Rightarrow x=\dfrac{23}{7}+\dfrac{9}{5}=\dfrac{115}{35}+\dfrac{36}{35}=\dfrac{151}{35}\)
c) \(...\Rightarrow x.\dfrac{7}{2}=\dfrac{19}{4}\Rightarrow x=\dfrac{19}{4}:\dfrac{7}{2}\Rightarrow x=\dfrac{19}{4}.\dfrac{2}{7}=\dfrac{19}{14}\)
d) \(...\Rightarrow x:\dfrac{8}{3}=\dfrac{13}{3}\Rightarrow x=\dfrac{13}{3}.\dfrac{8}{3}=\dfrac{124}{9}\)
(4x-3)4 = (4x-3)2
(4x-3)2. (4x-3)2= (4x-3)2
(4x-3)2= (4x-3)2 : (4x-3)2
(4x-3)2 =1
=> 4x-3 = 1
4x = 1+3
4x= 4
x= 1
Vậy...